2017
DOI: 10.1111/1467-9566.12530
|View full text |Cite
|
Sign up to set email alerts
|

Shifting dementia discourses from deficit to active citizenship

Abstract: Within western cultures, portrayals of dementia as 'a living death' are being challenged by people living with the diagnosis. Yet dementia remains one of the most feared conditions. The sociological lens of citizenship provides a conceptual framework for reviewing the role of society and culture in repositioning dementia away from deficit to a discourse of agency and interdependence. Awareness of cognitive change, and engaging with the diagnostic process, moves people into a transitional, or 'liminal' state of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 54 publications
1
105
0
Order By: Relevance
“…Similarly, dementia could lead individuals to move into a post‐liminal state as either active or passive citizens in the way they respond to the illness (Birt et al . ).…”
Section: Disrupted Illness Biographiesmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, dementia could lead individuals to move into a post‐liminal state as either active or passive citizens in the way they respond to the illness (Birt et al . ).…”
Section: Disrupted Illness Biographiesmentioning
confidence: 97%
“…Saunders (2018) found that people with sciatica rejected their diagnosis as representing 'the real me', sometimes leading to proactive illness management to assert control over symptoms. Similarly, dementia could lead individuals to move into a post-liminal state as either active or passive citizens in the way they respond to the illness (Birt et al 2017).…”
mentioning
confidence: 99%
“…The involvement of people living with dementia and their supporters and carers in the setting up, running, and monitoring of DFCs indicates their recognition as experts by experience or active agents able to direct, contribute, and participate. 17,36 There was evidence of involve-…”
Section: Involvement Of People Affected By Dementiamentioning
confidence: 99%
“…12 Calls for recognition of the human rights of people living with dementia have been growing louder in recent years. 2 This ranges from studies on what it means to be a citizen with dementia 16,17 to evaluations of communities' activities 18 and evaluations of dementia-sensitive infrastructure such as transport and the design of public and commercial buildings. 2 This ranges from studies on what it means to be a citizen with dementia 16,17 to evaluations of communities' activities 18 and evaluations of dementia-sensitive infrastructure such as transport and the design of public and commercial buildings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation